Analisis Miskonsepsi dalam Menyelesaikan Masalah Matematis pada Siswa Kelas VII SMP - Romadhany Surya Astuti; Wharyanti Ika Purwaningsih; Supriyono Supriyono (Jurnal Inovasi Pendidikan Matematika (JIPM), 2022)
This study aims to describe the misconceptions that occur to junior high school students in solving problems on algebraic fractions. The research method used is descriptive qualitative. The research was conducted at SMP Negeri 6 Purworejo class VII A with 2 students selected using a purposive technique with the category of students selected being moderately capable. Data collection techniques used in the form of diagnostic tests, interviews, and field notes. The research instrument used is a matter of diagnostic tests with data validity checking done by triangulation. The stages of data analysis are data reduction, data display, and conclusion drawing/verification. The results of the analysis on research and discussion can be concluded that students have misconceptions. Students experience misconceptions in the matter of algebraic arithmetic fractions. Misconceptions were also seen from students giving CRI scores to the answers that matched the students' level of confidence in answering the questions. According to the criteria of the CRI scale, it can be concluded that the results of students' answers are categorized as having misconceptions. These misconceptions are located when students answer the questions, resulting in: (1) translation misconceptions, (2) concept misconceptions, (3) strategy misconceptions, (4) systematic misconceptions, (5) sign misconceptions and (6) arithmetic misconceptions